Mechanical Properties and Structure of Novel Polymer Blends and Composites Fabricated by Reactive and High-shear Rotational Processing. (June 2016) - Ishigami, A.; Kodama, Y.; Suenaga, H.; Inoue, T.; Ito, H.
Abstract: Various polymer alloys have been examined to achieve performance beyond that of single polymers. Polyamide 6 (PA6) has extraordinary mechanical properties, impact absorbability, and high heat resistance necessary for exterior and interior automotive applications. Nevertheless, some materials and their combinations can exhibit inferior physical properties. This paper describes a novel polymer blend with PA6, fabricated using high-shear rotational processing. Modulated differential scanning calorimetry (M-DSC), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) elucidated thermal properties and morphologies of PA6 blends. Tensile and Izod tests revealed their mechanical properties. Results show that novel PA6 blends are useful for automotive applications.